HymenoKeys, an interactive matrix keys system to identify Hymenoptera families and Ichneumonidae subfamilies - Rousse, Pascal (Zootaxa, 2025)
The identification of higher taxa of Hymenoptera is often challenging. It relies on dichotomous keys, very few of them covering the whole order. Moreover, Hymenoptera taxonomy has greatly changed during the past 30 years, making these few tools outdated. To my knowledge, no geographically and taxonomically comprehensive interactive key exists for the order. To address this, Hymenokeys, a set of interactive keys developed on the XPer3 platform, is presented and its expected outputs discussed. It includes all currently described hymenopteran families and the subfamilies of Ichneumonidae. The ambition is for this to be an open access, user-friendly, reliable and evolving tool for diagnosticians, to complement the existing classical dichotomous keys.